Coping with stress of family caregivers of cancer patients in Turkey - Elanur Yιlmaz Karabulutlu (Elsevier, 2014)
Objective: Cancer is a disease that not only affects the individual's mental and physical integrity but also affects the functionality of the family system. Caregivers experience stress when patients cannot cope with the symptoms they are experiencing. The stress experienced by caregivers gives rise to psychological and physical symptoms. The purpose of this study is to determine the attitude of coping with stress of family caregivers of cancer patients. Methods: This study was conducted as a descriptive research at the Medical Oncology Clinic. The study sample group comprised of 127 family caregivers. In the collection of the data, the Personel Information Form and Attitude of Coping with Stress Inventory were used. Results: The coping attitude used most frequently by family caregivers was active planning, and the least used coping attitude was avoidance isolation (biochemical). There was no significant statistical difference between the coping attitude depending on the descriptive characteristics of the family caregivers (P > 0.05). Conclusion: Results show that family caregivers of cancer patients tend to choose effective coping methods. However, there were still caregivers that displayed ineffective coping attitudes. Therefore, it is important to support the effective coping attitudes of caregivers and intervene in order to change the ineffective coping attitudes.